FROM TRADITION TO TRANSFORMATION: A REVIEW OF MODERN CORPORATE BUDGETING APPROACHES - Lasmiyati, Lasmiyati (Gema Kampus IISIP YAPIS Biak, 2025)
This literature review explores the transformation of corporate budgeting approaches from traditional to modern frameworks. Conventional budgeting, once dominant for its control and predictability, is increasingly challenged by rapidly changing business environments. In contrast, modern approaches such as performance-based, flexible, rolling, and risk-based budgeting offer agility and strategic alignment. The study synthesizes findings from global and regional literature to identify key shifts, implementation challenges, and financial implications. It highlights the importance of adaptive budgeting systems in improving cost efficiency, responsiveness, and financial resilience. The review concludes that while traditional budgeting retains certain merits, transformative approaches are essential in dynamic economic contexts. Furthermore, this review serves as a foundation for organizations to critically evaluate their financial planning systems and adopt best practices suited for contemporary challenges.